Homing wellness: can narrative design transform living spaces for people with dementia into engaging environments enabling communication? - Minetou, Loukia; Chatzopoulos, Avraam; Tzerachoglou, Anastasios; Priniotakis, Georgios; van Hoof, Joost; Sfyroera, Emmanouela; Georgiadou, Zoe; Tyrovola, Styliani; Drosos, Christos (Frontiers in Public Health, 2024)
Interactive design is an emerging trend in dementia care environments. This article describes a research project aiming at the design and development of novel spatial objects with narrative attributes that incorporate embedded technology and textiles to support the wellbeing of people living with dementia. In collaboration with people with dementia, this interdisciplinary research project focuses on the question of how innovative spatial objects can be incorporated into dementia long-term care settings, transforming the space into a comforting and playful narrative environment that can enhance self-esteem while also facilitating communication between people living with dementia, family, and staff members. The research methodologies applied are qualitative, including Action Research. Participatory design methods with the experts by experience—the people with dementia—and health professionals have been used to inform the study. Early findings from this research are presented as design solutions comprising a series of spatial object prototypes with embedded technology and textiles. The prototypes were evaluated primarily by researchers, health professionals, academics, and design practitioners in terms of functionality, aesthetics, and their potential to stimulate engagement. The research is ongoing, and the aim is to evaluate the prototypes by using ethnographic and sensory ethnography methods and, consequently, further develop them through co-design workshops with people living with dementia.